Influence of maternal risk perception and vaccination knowledge on childhood vaccination intentions - Md suhaimi, Teh Muthmainnah; Ismail, Aniza; Ismail, Rohani; Rasudin, Nur Syahmina; Mohd Noor, Norhayati; Jayapalan, Ashvini; Suli, Zailiza; Mohd Nazori, Mohd Nazir (Springer Nature, 2025)
Background Vaccine hesitancy remains a significant barrier to effective public health strategies aimed at overcoming the resurgence of vaccine-preventable diseases globally. This study aims to explore the roles of maternal knowledge, risk perception, health self-efficacy, and demographic characteristics in influencing the intention of antenatal mothers to accept childhood vaccination for their newborns.